Preparation method and equipment of spherical oxide particles
By combining carbon nanotubes and boron oxide, and utilizing electrostatic adsorption and high-temperature sintering techniques, the problem of preparing spherical oxide particles has been solved, enabling efficient and low-cost preparation and large-scale production of nanoparticles suitable for applications such as corrosion resistance and lubrication.
Patent Information
- Application Number
- CN202510830897.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-20
- Publication Date
- 2025-10-17
AI Technical Summary
Existing technologies suffer from problems such as high equipment requirements, high production costs, complex post-processing, difficulty in scaling up, numerous defects in nanoparticle structure, poor spherical morphology of products, and inability to meet application requirements such as corrosion resistance and lubrication.
Spherical oxide particles were prepared by using carbon nanotubes (CNTs) as templates, combined with morphology regulation and electrostatic adsorption technology of boron oxide (B2O3), and through high-temperature sintering and ultrasonic separation.
This technology enables the homogenization and large-scale production of spherical oxide particles, reduces production costs, improves the crystallinity and applicability of the product, and meets the needs of harsh applications such as corrosion resistance and lubrication.
Smart Images

Figure HDA0005459325910000011 
Figure HDA0005459325910000012 
Figure HDA0005459325910000021
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a method and equipment for preparing spherical oxide particles. Background Art
[0002] Nanomaterials, due to their unique physical and chemical properties, are widely used in catalysis, optoelectronics, sensors, and biomedicine. Currently, the main methods for preparing spherical oxide nanoparticles include sol-gel, hydrothermal, vapor deposition, and microemulsion methods.
[0003] The sol-gel method uses compounds containing highly chemically active components as precursors. The raw materials are uniformly mixed in a liquid phase, hydrolyzed and condensed to form a stable, transparent sol, which is then aged to form a gel with a three-dimensional network structure. Finally, the nanomaterial is dried and sintered to solidify. This method has the advantages of a rich variety of reactants, uniform product particles, and easy process control. It can produce a variety of oxides with excellent product uniformity and high chemical purity, but the preparation process is relatively complex and expensive. The hydrothermal method involves placing the reactants in a fluid such as an aqueous solution or steam for a chemical reaction under high temperature and pressure, followed by separation and heat treatment to produce nanoparticles. This method produces products of high purity, good dispersibility, and easy-to-control particle size, but requires a high temperature and high pressure reaction environment, placing high demands on equipment. The vapor deposition method uses chemical reactions of metal compound vapors to synthesize nanomaterials. This method produces products of high purity and a narrow particle size distribution, but it also requires high equipment requirements and is relatively expensive. The microemulsion method refers to the formation of an emulsion in which two immiscible solvents are reacted with surfactants. Nanoparticles are obtained in tiny droplets after nucleation, coalescence, agglomeration, and heat treatment. This method has good monodispersity, easy-to-control particle size, and good interfacial properties, but requires a large amount of organic solvents and surfactants, and the separation process is relatively cumbersome.
[0004] Therefore, there is an urgent need to develop a complete process flow and equipment to facilitate the large-scale production of oxide nanoparticles, so as to solve the problems existing in the existing technology, such as high equipment requirements, high production costs, complex post-processing, difficulty in scalability, many structural defects of nanoparticles, poor spherical morphology of products, and inability to meet application requirements in terms of corrosion resistance and lubrication. Summary of the Invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems in the prior art. To this end, one of the purposes of the present invention is to provide a method for preparing spherical oxide particles.
[0006] A second object of the present invention is to provide spherical oxide particles.
[0007] A third object of the present invention is to provide a device for implementing the above-mentioned preparation method.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is:
[0009] A first aspect of the present invention provides a method for preparing spherical oxide particles, comprising the following steps:
[0010] S1, causing the electrode with carbon nanotubes deposited on the surface to electrostatically adsorb boron oxide particles, and sintering once to obtain a substrate;
[0011] S2. Allow the substrate to electrostatically adsorb the functional structural oxide, perform secondary sintering, and then place the substrate in water for ultrasonic treatment to obtain the spherical oxide particles.
[0012] In some embodiments of the present invention, in step S1, the electrode is selected from a metal electrode or a conductive ceramic electrode.
[0013] In some preferred embodiments of the present invention, the metal electrode is selected from a stainless steel electrode, a nickel electrode, a titanium electrode or a platinum electrode.
[0014] In some preferred embodiments of the present invention, the conductive ceramic electrode is selected from an alumina ceramic electrode or a silicon carbide ceramic electrode with a conductive layer coated on the surface.
[0015] In some embodiments of the present invention, in step S1 , the surface roughness of the electrode is Ra≤0.2 μm.
[0016] Specifically, the present invention has no special requirements for the electrodes used to deposit carbon nanotubes. Apart from the above, any other flat and high-temperature-resistant electrodes can be used. Furthermore, the surface roughness of the electrodes, Ra ≤ 0.2 μm, is more conducive to ensuring uniform carbon nanotube deposition.
[0017] In some embodiments of the present invention, in step S1, the deposition thickness of the carbon nanotubes is 10-100 μm.
[0018] In some embodiments of the present invention, in step S1, the carbon nanotubes are deposited by electrochemical deposition.
[0019] Specifically, the present invention limits the deposition thickness of carbon nanotubes. The thinner the carbon nanotube layer, the higher the utilization rate. However, if the deposited layer is too thin, it will be difficult to form a uniform mixed coating, affecting the subsequent precipitation of oxide nanoparticles, and the thin layer is easily damaged after multiple high-temperature sintering, resulting in a reduction in the number of times the substrate can be reused. If the deposited layer is too thick, it will not only significantly increase the time and cost of electrochemical deposition, but also weaken the external electric field during electrostatic adsorption, reducing the adsorption efficiency of boron oxide or functional structural oxide particles. At the same time, it may also cause local insufficient reaction due to uneven heat transfer, resulting in structural defects.
[0020] In some embodiments of the present application, in step S1, the temperature of the primary sintering is 400-600℃.
[0021] In some embodiments of the present application, in step S2, the functional structure oxide is selected from at least one of SiO2, TiO2, ZnO, Al2O3, MgO.
[0022] In some embodiments of the present application, in step S2, the temperature of the secondary sintering is 600-1300℃.
[0023] In some preferred embodiments of the present application, in step S2, when the substrate electrostatically adsorbs SiO2, the temperature of the secondary sintering is 700-850℃.
[0024] In some preferred embodiments of the present application, in step S2, when the substrate electrostatically adsorbs TiO2, the temperature of the secondary sintering is 950-1100℃.
[0025] In some preferred embodiments of the present application, in step S2, when the substrate electrostatically adsorbs ZnO, the temperature of the secondary sintering is 700-850℃.
[0026] In some preferred embodiments of the present application, in step S2, when the substrate electrostatically adsorbs Al2O3, the temperature of the secondary sintering is 700-850℃.
[0027] In some preferred embodiments of the present application, in step S2, when the substrate electrostatically adsorbs MgO, the temperature of the secondary sintering is 650-800℃.
[0028] In some embodiments of the present application, in step S2, the parameters of the ultrasonic treatment include at least one of the following parameters: the ultrasonic power is 80-100W, the ultrasonic frequency is 2-3 times, and the ultrasonic time is 8-10min / time.
[0029] In some embodiments of the present application, in step S2, during the ultrasonic treatment, the interval cooling time between two ultrasonic treatments is 3-5min.
[0030] In some embodiments of the present application, in step S2, the total duration of the ultrasonic treatment is less than or equal to 30min.
[0031] Specifically, to avoid local overheating caused by long-time continuous ultrasonic, which leads to the increase of the surface energy of nanoparticles, promotes secondary agglomeration, and the uneven solution cavitation effect, the large particles are not dispersed in time after breaking, and the problem of re-aggregation, the application adopts multiple ultrasonic mode, and short-time treatment of 8-10 minutes each time can effectively break the initial agglomerates, and interval cooling can avoid solution temperature accumulation and maintain particle stability; the total length of ultrasonic treatment is controlled to be less than or equal to 30 minutes, which can avoid particle agglomeration or structure damage.
[0032] In some embodiments of the application, in step S2, the ultrasonic treatment adopts a probe-type ultrasonic instrument or a water bath-type ultrasonic instrument.
[0033] In some embodiments of the application, after the ultrasonic treatment in step S2, a drying operation is further included.
[0034] In some embodiments of the application, in steps S1 and S2, the parameters of electrostatic adsorption include at least one of the following parameters: the voltage is 2-10kV, the plate spacing is 20-50mm, and the time is 5-10s.
[0035] Specifically, the application adopts the electrostatic adsorption method to adsorb boron oxide particles and functional structure oxides, and provides sufficient electric field force through 2-10kV voltage. When the voltage is too low (less than 2kV), the electric field strength is insufficient, the particles cannot be effectively adsorbed, resulting in uneven coating. When the voltage is too high (more than 10KV), air breakdown discharge may be caused (especially when the plate spacing is small), which destroys the process stability. Accordingly, the plate spacing is controlled to be 20-50mm. When the spacing is too small (less than 20mm), the electric field strength is too high, which easily leads to air breakdown or particle accumulation, affecting the subsequent sintering effect. When the spacing is too large (more than 50mm), the electric field strength decays, and the adsorption efficiency decreases, which is difficult to realize the uniformity required for large-scale production. In addition, the time of electrostatic adsorption is controlled to be 5-10s, which can balance the adsorption efficiency and quality. When the time is too short (less than 5s), the particle adsorption amount is insufficient, and a continuous coating cannot be formed. When the time is too long (more than 10s), the particles may be excessively accumulated, affecting the uniformity of boron oxide and carbon nanotube infiltration.
[0036] The basic principle of the application is as follows:
[0037] The application realizes the spheroidization, uniformization and large-scale preparation of oxide nanoparticles by the template effect of carbon nanotubes (CNTs) and the morphological regulation effect of boron oxide (B2O3), combined with electrostatic adsorption and high-temperature sintering technology. The specific principle can be divided into the following key stages:
[0038] (1) Template effect of CNTs substrate: A 10-100 μm thick CNTs layer is electrochemically deposited on a conductive substrate to form a porous and high specific surface area template, the three-dimensional network structure of CNTs provides a uniform carrier for the subsequent adsorption of B2O3 and functional structural oxide particles, and limits the growth direction of the particles to promote the formation of spherical morphology; a CNTs layer that is too thin (less than 10 μm) will result in insufficient carrier strength, and a CNTs layer that is too thick (more than 100 μm) will reduce the adsorption efficiency of the electric field;
[0039] (2) Morphology control and infiltration of B2O3: B2O3 particles are adsorbed to the surface of the CNTs substrate under a high-voltage electric field (2-10 kV), and B2O3 is melted at a high temperature (400-600°C) to form a fully infiltrated mixed coating with CNTs; the glassy nature of B2O3 enables it to uniformly coat CNTs in the molten state and promote the precipitation of functional structural oxide particles upon cooling through volume shrinkage and phase separation;
[0040] (3) Adsorption and melting-precipitation of functional structural oxide particles: functional structural oxide particles such as SiO2, TiO2, ZnO, Al2O3, and MgO are adsorbed to the B2O3-CNTs composite coating, and at a specific temperature, the functional structural oxide forms a eutectic with B2O3; upon cooling, B2O3 separates from the functional structural oxide due to the difference in thermal expansion coefficient, but due to the blocking effect of CNTs, the functional structural oxide melt shrinks into spherical particles through surface tension, and the confinement effect of CNTs and the interfacial energy control of B2O3 together ensure the sphericity and monodispersity of the particles;
[0041] (4) Ultrasonic separation and substrate reuse: after sintering, the substrate is immersed in an aqueous solution, and spherical nanoparticles are detached from the surface of CNTs through ultrasonic cavitation (80-100 W, 2-3 times); this process avoids long-term ultrasonic treatment that can cause particle agglomeration or structural damage; after the nanoparticles are detached, the CNTs substrate can be reused, reducing production costs.
[0042] The second aspect of the present application provides a spherical oxide particle prepared by the method of the first aspect of the present application.
[0043] In some embodiments of the present application, the particle size of the spherical oxide particle is 20-500 nm.
[0044] The third aspect of the present application provides a device for implementing the method of the first aspect of the present application, comprising:
[0045] The device shell 1, the large particle settling device 2, the horizontal flow layering device 3, the electrostatic adsorption device 4, the dust recovery device 6 and the sintering system; wherein the large particle settling device 2 settles particles with a diameter of greater than or equal to 0.2 microns; the electrostatic adsorption device 4 comprises an electrostatic adsorption plate 5; and the dust recovery device 6 recovers unadsorbed particles.
[0046] In some embodiments of the application, the device further comprises an ultrasonic treatment zone.
[0047] In some embodiments of the application, the sintering system comprises a temperature control device, and the secondary sintering temperature is selected by the type of functional structural oxide particles.
[0048] Specifically, the working principle of the device is as follows:
[0049] The device provided by the application is mainly used for the preparation of a CNTs substrate, electrostatic adsorption, high-temperature sintering and the separation and recovery of nanoparticles. The core components thereof include: a device shell 1, a large particle settling device 2, a horizontal flow layering device 3, an electrostatic adsorption device 4 and a dust recovery device 6, wherein:
[0050] (1) The device shell 1 is used to provide a closed environment to avoid external pollution; in the CNTs substrate preparation stage, the electrostatic adsorption device 4 is mainly used to place an electrode in the device as a cathode, to pass electricity in an electrolyte, to form a CNTs layer on the substrate by electrochemical deposition, and to generate a high-voltage electric field on the electrostatic adsorption plate 5 after the electrostatic adsorption device 4 is electrified, so that B2O3 particles are charged and adsorbed to the surface of the CNTs substrate in the electric field, particles with a diameter of greater than or equal to 0.2 microns are settled into the large particle settling device 2 due to gravity or centrifugal force, so as to avoid affecting the adsorption quality, and qualified particles with a diameter of less than 0.2 microns are uniformly adsorbed to the substrate after being stabilized by the airflow (air) of the horizontal flow layering device 4; the CNTs substrate adsorbed with B2O3 is sent to the sintering system of the device, the device shell 1 provides a closed high-temperature environment to prevent oxidation, and B2O3 is fully infiltrated with CNTs after sintering to form a mixed coating;
[0051] (2) Then, the electrostatic adsorption step is repeated by using the electrostatic adsorption device 4 to adsorb functional structural oxide particles to the substrate after sintering, unadsorbed large particles or agglomerates fall into the dust recovery device 8 to realize the recycling of materials; the substrate adsorbed with functional structural oxide particles is again sent to the sintering system of the device to make the functional structural oxide particles melt and precipitate on the surface of the CNTs; then the substrate is sent to the ultrasonic treatment zone to use the ultrasonic cavitation effect to strip the nanoparticles from the substrate, the dust recovery device 8 collects the residual particles, and the substrate can be reused.
[0052] Compared with the prior art, the device provided by the application has the following beneficial effects:
[0053] 1) The application provides a preparation method of spherical oxide particles, which utilizes the morphological change of B2O3 at high temperature and the physical barrier effect of CNTs to force the functional structural oxide melt to form spherical particles spontaneously through surface tension, solving the problems of poor sphericity and uneven dispersion in traditional methods. Through the synergistic design of electrostatic adsorption and fractional ultrasonic, the production cycle is significantly shortened, the substrate can be reused, and the material cost is reduced. The melting-extraction mechanism avoids the hydrolysis condensation defects common in chemical methods, and the product has high crystallinity, which is suitable for harsh application scenarios such as corrosion resistance and lubrication. By adjusting the secondary sintering temperature, various types of oxide nanospheres can be prepared to meet diversified needs.
[0054] 2) The preparation device of the spherical oxide particles provided by the application integrates an electrostatic adsorption device, a dust recovery system and a large particle settling device, can process large-size substrates at a time, and has the capacity for large-scale production. The dust recovery device can capture unadsorbed particles, improve material utilization, and has no harmful solvent emission throughout the process, meeting the requirements of green production. BRIEF DESCRIPTION OF DRAWINGS
[0055] Figure 1 It is a process flow chart of the preparation method of the spherical oxide particles of the application.
[0056] Figure 2 It is a partial component schematic diagram of the spherical oxide particle preparation device in the embodiment, wherein 1 is a device shell, 2 is a large particle settling device, 3 is a laminar stratification device, 4 is an electrostatic adsorption device, 5 is an electrostatic adsorption plate, and 6 is a dust recovery device.
[0057] Figure 3 It is a photo of the CNT substrate prepared by electrochemical deposition in Example 1.
[0058] Figure 4 It is an electron microscope graph of the SiO2 nanosphere particles prepared in Example 1. DETAILED DESCRIPTION
[0059] The content of the application will be further described in detail through specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples can be obtained from conventional commercial channels or can be obtained by existing technical methods. Unless otherwise specified, the test or test method is a conventional method in the art.
[0060] Figure 1 It is a process flow chart of the preparation method of the spherical oxide particles of the application, Figure 2Figure 1 is a schematic diagram of part of the equipment used to prepare the spherical oxide particles in the examples, in which 1 is the equipment housing, 2 is the large particle settling device, 3 is the laminar flow separation device, 4 is the electrostatic adsorption device, 5 is the electrostatic adsorption plate, and 6 is the dust recovery device. During the preparation process, the electrostatic adsorption device 4 is powered, the electrostatic adsorption plate 5 generates a high-voltage electric field, the B2O3 particles are charged in the electric field and are adsorbed onto the surface of the CNTs substrate. The particles with a diameter of ≥0.2 μm settle into the large particle settling device 2 due to gravity or centrifugal force, thereby avoiding affecting the adsorption quality. The qualified particles with a diameter of <0.2 μm are uniformly adsorbed onto the substrate after being stabilized by the air flow of the laminar flow separation device 4. The CNTs substrate adsorbed with B2O3 is sintered in a sintering system. The equipment housing 1 provides a sealed high-temperature environment to prevent oxidation. After sintering, the B2O3 is fully infiltrated with the CNTs to form a mixed coating. Subsequently, the electrostatic adsorption step is repeated using the electrostatic adsorption device 4 to adsorb SiO2 particles onto the sintered substrate. The unadsorbed large particles or agglomerates fall into the dust recovery device 8, thereby achieving the recycling of the materials. The substrate adsorbed with SiO2 particles is again fed into the sintering system of the equipment to melt the SiO2 particles and precipitate them on the surface of the CNTs. Subsequently, the substrate is fed into an ultrasonic treatment zone to separate the SiO2 nanosphere particles from the substrate using the ultrasonic cavitation effect. The dust recovery device 8 collects the residual particles, and the substrate can be reused.
[0061] The following will describe the preparation of the spherical oxide particles in the examples by combining Figure 1 and Figure 2
[0062] Example 1
[0063] In this example, a SiO2 nanosphere particle is prepared by the following steps:
[0064] S11. A stainless steel electrode with a surface roughness Ra≤0.2 μm is selected, and is ultrasonically cleaned with acetone, ethanol and deionized water in sequence to remove surface grease and oxides. A 20-30 μm thick CNTs layer is deposited on the surface of the stainless steel electrode by electrochemical deposition to obtain a CNTs substrate.
[0065] S12. The CNTs substrate is electrostatically adsorbed with B2O3 particles at a voltage of 10 kV and a plate spacing of 50 mm for 10 s. Subsequently, the B2O3-CNTs substrate is sintered at 500°C once to obtain a B2O3-CNTs substrate.
[0066] S21. The B2O3-CNTs substrate is electrostatically adsorbed with SiO2 particles. Subsequently, the B2O3-CNTs substrate is sintered at 700-850°C twice.
[0067] S22, the sintered substrate is placed in water, and is put into a probe-type ultrasonic instrument for ultrasonic treatment, the ultrasonic power is 80 W, the ultrasonic frequency is 2 times, and the ultrasonic time is 8 min / time, the nanospheres are separated into a solution, the solution is dried, and SiO2nanosphere particles are obtained.
[0068] Example 2
[0069] In this example, TiO2nanosphere particles are prepared, and the steps are as follows:
[0070] S11, a stainless steel electrode with a surface roughness Ra≤0.2 μm and a smooth surface is selected, is ultrasonically cleaned with acetone, ethanol and deionized water in sequence to remove surface grease and oxides, and a 50-60 μm thick CNTs layer is deposited on the surface of the stainless steel electrode by electrochemical deposition to obtain a CNTs substrate;
[0071] S12, B2O3particles are electrostatically adsorbed on the CNTs substrate, the voltage is 2 kV, the electrode plate spacing is 30 mm, and the time is 5 s, and then the B2O3-CNTs substrate is sintered at 500 ℃ once,
[0072] S21, TiO2particles are electrostatically adsorbed on the B2O3-CNTs substrate, and then the B2O3-CNTs substrate is sintered at 950-1100 ℃ twice;
[0073] S22, the sintered substrate is placed in water, and is put into a probe-type ultrasonic instrument for ultrasonic treatment, the ultrasonic power is 100 W, the ultrasonic frequency is 3 times, and the ultrasonic time is 10 min / time, the nanospheres are separated into a solution, the solution is dried, and TiO2nanosphere particles are obtained.
[0074] Figure 3 The photograph of the CNTs substrate prepared by electrochemical deposition in Example 1 is shown in FIG. 1. Figure 3 It can be known from FIG. 1 that a uniform CNTs layer is formed on the surface of the stainless steel electrode by electrochemical deposition.
[0075] Figure 4 The electron microscope images of the SiO2nanosphere particles prepared in Example 1 are shown in FIG. 2, wherein, Figure 4 (a) and (b) in FIG. 2 are electron microscope images of the SiO2nanosphere particles at different magnifications, and it can be known from FIG. 2 that the SiO2nanosphere particles are successfully prepared in Example 1, the particle size is about 20-500 nm, the sphericity of the particles is high, there is no aggregation phenomenon, the dispersibility is good, the preparation process is simple, the equipment cost is low, and the particles have the potential for large-scale production. Figure 4 (a) and (b) in FIG. 2 are electron microscope images of the SiO2nanosphere particles at different magnifications, and it can be known from FIG. 2 that the SiO2nanosphere particles are successfully prepared in Example 1, the particle size is about 20-500 nm, the sphericity of the particles is high, there is no aggregation phenomenon, the dispersibility is good, the preparation process is simple, the equipment cost is low, and the particles have the potential for large-scale production.
Claims
1. A method for preparing spherical oxide particles, characterized in that: The following steps are involved: S1, causing the electrode with carbon nanotubes deposited on the surface to electrostatically adsorb boron oxide particles, and sintering once to obtain a substrate; S2. Allow the substrate to electrostatically adsorb the functional structural oxide, perform secondary sintering, and then place the substrate in water for ultrasonic treatment to obtain the spherical oxide particles.
2. The preparation method according to claim 1, characterized in that In step S1, the deposition thickness of the carbon nanotubes is 10-100 μm.
3. The preparation method according to claim 1, characterized in that In step S1, the primary sintering temperature is 400-600°C.
4. The preparation method according to claim 1, characterized in that In step S2, the functional structural oxide is selected from at least one of SiO2, TiO2, ZnO, Al2O3, and MgO.
5. The preparation method according to claim 1, characterized in that In step S2, the temperature of the secondary sintering is 600-1300°C.
6. The preparation method according to claim 1, characterized in that In step S2, the parameters of the ultrasonic treatment include at least one of the following parameters: ultrasonic power of 80-100 W, ultrasonic times of 2-3 times, and ultrasonic time of 8-10 min / time.
7. The preparation method according to claim 1, characterized in that In steps S1 and S2, the electrostatic adsorption parameters include at least one of the following parameters: voltage of 2-10 kV, plate spacing of 20-50 mm, and time of 5-10 s.
8. A spherical oxide particle, characterized in that: The method comprises adopting the preparation method according to any one of claims 1 to 7.
9. The spherical oxide particles according to claim 8, characterized in that The particle size of the spherical oxide particles is 20-500 nm.
10. An apparatus for implementing the preparation method according to any one of claims 1 to 7, characterized in that: include Equipment housing (1), large particle settling device (2), stratostratification device (3), electrostatic adsorption device (4), dust recovery device (6) and sintering system; wherein the large particle settling device (2) settles particles with a diameter of ≥0.2 μm; the electrostatic adsorption device (4) includes an electrostatic adsorption plate (5); and the dust recovery device (6) recovers unadsorbed particles.